The effect of HIV and the modifying effect of anti-retroviral therapy (ART) on body mass index (BMI) and blood pressure levels in rural South Africa - Feigl, Andrea B.; Bloom, David E.; Danaei, Goodarz; Pillay, Deenan; Salomon, Joshua A.; Tanser, Frank; Bärnighausen, Till (PLOS ONE, 2016)
Background High BMI and blood pressure are leading chronic disease risk factors in South Africa. Longterm effects of HIV and ART on adiposity and blood pressure are poorly understood, and direct comparisons of risk factor trajectories in HIV- versus HIV+ populations are rare. Methods In 2003 and 2010, height, weight, and blood pressure were recorded in a study population (n = 505) in KwaZulu-Natal, South Africa (30% adult HIV prevalence). We modeled change in BMI and BP longitudinally in HIV- individuals (n = 315), seroconverters (n = 32), HIV+ patients not on ART (HIV+ART−; n = 52), HIV+ patients on ART for 0-<2 years as of 2010 (HIV+ART0-<2 yrs; n = 18), patients on ART for 2-5 years (HIV+ART2-5yrs; n = 44), and a subgroup with unknown HIV status (n = 44). Difference-in-differences were assessed in reference to the HIV- population. Results Between 2003 and 2010, BMI increased significantly in the HIV- group, by 0.874 (95% CI 0.339, 1.41; p = 0.001), to 30.4. BMI drop was significantly greater in HIV+ART0-<2yrs than in HIV+ART2-5yrs (p = 0.005). DID in BMI in HIV+ART0-<2yrs versus the reference was -5.21 (95% CI -7.53, -2.90; p = 0.001), and DID in HIV+ART2-5yrs versus reference was -1.35 (95% CI -2.89, 0.189; p = 0.086). DID in SBP in HIV+ART−vs HIV- DID was -7.55 mmHg (95% CI -13.2 to -1.90; p = 0.009). Conclusion Short-term ART (0-<2 years) was associated with larger weight loss than either no ART or long-term ART. Once on ART for 2+ years, individuals ‘caught up’ on weight gain with the HIV- population. Our results showcase the importance of health system readiness to address the burgeoning double burden of disease in South Africa.
Gesehen am 14.05.2020